PEMETAAN MASALAH DAN PEMBERIAN KONSELING BAGI MAHASISWA DENGAN INDEKS PRESTASI RENDAH - Shanty Sudarji; Linda Linda; Dina Argitha (Universitas Bunda Mulia, 2014)
PP No. 30 of 1990 on Higher Education defines that the student is enrolled learners and gain knowledge on a particular college, the institution aims to prepare students to be members of the community who have the academic ability and or professionals who can apply, develop and or create science knowledge, technology, and or art. College world is a new world, different from the high school days. Although some teenagers will still live with parents, self-reliance becomes absolutely necessary in managing studies in college. The problems faced by students, especially new students are varied, ranging from adjustment problems, problems in relationships with fellow students, problems with assignments, problems with teachers, and so forth. All kinds of problems faced by students can influence acquisition performance index achieved during one semester. Counseling is one of services that can be provided for students with low GPA. The method in this study is qualitative. Based on the results obtained with the sample number as many as 70 students, obtained a picture of the problem is as follows: 45.7% for introspection disability issues, 21.4% self-concept and family problems, motivational problems 18.6%, 8.6% learning time management issues, and issues of interest by 5.7%. Counseling include steps proposed by Brammer and MacDonald (2003) covers the determination of problems and goals; problem solving, decision making and planning and behavior change. Keywords: mapping problems, low GPA, counseling